The Influence of the Dietary Protein Content on Growth in Giant Breed Dogs - Nap, R. C.; Hazewinkel, H. A. W.; Voorhout, G.; Biewenga, W. J.; Koeman, J. P.; Goedegebuure, S. A.; Klooster, van t A. Th. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
Feeding immature dogs of large breeds a diet exceeding the NRC recommendations (5) for energy, protein, calcium (Ca), phosphorus (P), and vitamin D may result in disturbances of skeletal development. The effects of excess energy and various Ca:P ratios per se have been reported. The role of dietary protein, especially with regard to skeletal growth in giantbreed dogs was studied. Clinical, biochemical, radiographical, and histological parameters were studied in three groups of Great Dane pups raised on diets only differing in protein content (14.6, 23.1 and 31.6% dm respectively). Significant differences were found for body weight, plasma albumin, and plasma urea. The differences in protein intake per se had no demonstrable consequences for renal and skeletal development. A causative role for dietary protein in disturbed enchondral ossification in dogs is unlikely.Nutrition is important during growth, especially in giant breed dogs. The role of dietary protein with regard to skeletal development was studied in three groups of Great Dane pups raised on diets only differing in protein content. A causative role for dietary protein in disturbed enchondral ossification is unlikely.
Keywords: Dog; protein; growth; osteochondrosis; kidney